Management power of renewable energy in multiple sources system to feeding the rotor of a doubly-fed induction generator - Kendzi Mohammed; Aissaoui Abdelghani; Younes Dris; Bouiri Abdesselam; Haddar Mabrouk (Institute of Advanced Engineering and Science, 2023)
The purpose of this paper is the elimination of interruptions of electrical energy produced by a multi-source production system, so we have assured the feed of DFIG rotor in a wind system by different energy sources (photovoltaic generator, battery group) and switchover between them by auxiliary contacts controlled by a supervisor via a power control algorithm. For the photovoltaic generator, a controller for tracking the maximum power point is designed using direct search approach perturb observe method. For the battery group, the installation of a number of the capacitor battery elements in series and in parallel will be kept the power necessary to supply the DFIG rotor. For the wind system, it contains the power generated by DFIG is controlled by sliding mode system. With regard to switching between electrical energy sources, our proposed system relies on an algorithm to compare the energies produced by each generator with the energy required to feed the DFIG rotor and the energies consumed in the system, where the energy source with high production energy and available is exploited to feed the system and charge the batteries. Simulations were performed to confirm the reliability and efficacy of the system proposed.